2015
DOI: 10.1038/onc.2015.142
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HER3 monoclonal antibody patritumab sensitizes refractory non-small cell lung cancer to the epidermal growth factor receptor inhibitor erlotinib

Abstract: Human epidermal growth factor receptor (HER) 3 is aberrantly overexpressed and correlates with poor prognosis in non-small cell lung cancer (NSCLC). Patritumab is a monoclonal antibody against HER3 that has shown promising results in early-phase clinical trials, but an optimal target population for the drug has yet to be identified. In the present study, we examined whether heregulin, a HER3 ligand that is also overexpressed in a subset of NSCLC, can be used as a biomarker to predict the antitumorigenic effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 37 publications
4
85
0
Order By: Relevance
“…Recently, a common mechanism of acquired resistance to EGFR TKIs has been reported as a result of an RTK switch, such as amplification of MET [50,51] or HER2 [52, 53] or activation of HER3 [75, 76], insulin-like growth factor 1 receptor (IGF-1R) [77, 78], or fibroblast growth factor receptor 1 (FGFR1) [79, 80]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a common mechanism of acquired resistance to EGFR TKIs has been reported as a result of an RTK switch, such as amplification of MET [50,51] or HER2 [52, 53] or activation of HER3 [75, 76], insulin-like growth factor 1 receptor (IGF-1R) [77, 78], or fibroblast growth factor receptor 1 (FGFR1) [79, 80]. …”
Section: Resultsmentioning
confidence: 99%
“…HER3 is activated independent of MET amplification in NSCLCs, and may contribute acquired drug resistance to EGFR TKI [75, 76]. HER3 lacks several catalytically important residues and is thought to be an inactive pseudokinase [82].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of that, genes implicated in the emergence and progression of cancer have similar expression patterns in cancer cell lines and tumors, which validate the usefulness of the cell lines as an in vitro model of the tumors. The A549 adenocarcinoma and the SW900 squamous carcinoma cell lines are among the most commonly studied in lung cancer research and are widely used in terms of basic mechanisms of lung cancer and as pre-clinical in vitro models for drug sensitivity and effectiveness[9194]. Past studies have focused in the comparative characterization between lung tumors and the corresponding derived cell lines in terms of morphology, genotyping, gene expression and protein abundance[95–97].…”
Section: Resultsmentioning
confidence: 99%
“…Even so, 5-year survival rate is only 16%, though new drugs of anti-lung cancer such as angiogenesis-targeted drugs, epidermal growth factor receptor (EGFR)-targeted drugs, protein peptides of anti-lung cancer and lung cancer antibody drugs were developed. [97][98][99][100][101][102] Recently, a study reported that nanoliposomes using sodium hyaluronate and trimethyl CS form polymer-glycerosomes that can effectively deliver CUR to lung so as to improve the therapeutic index of CUR. 103 Recently, many studies reported that CUR liposomes have anticancer activity.…”
Section: Lung Cancermentioning
confidence: 99%